A Case Report on Laryngeal histoplasmosis masquerading as Tuberculosis (Bangladesh Journal of Medicine, 2024)
Immunocompromised patients typically develop laryngeal histoplasmosis as a result of the fungus spreading from the lungs to other organs. Primary isolated laryngeal histoplasmosis is uncommon. We reported a unique case of laryngeal histoplasmosis in a 25-year-old male who initially had a preliminary diagnosis of tuberculosis. A 25-year-old man complained of dysphagia and increasing hoarseness of voice for three months when he first came into the medical department. He has also had a cough and intermittent fever for 1 month. Bilateral post-TB fibrosis with bronchiectasis, a consequence of pulmonary tuberculosis infection, was the patient’s previous diagnosis. In addition to that, he is also receiving treatment for his chronic calcific pancreatitis with pancreatic enzyme supplements and dietary modifications. During physical examination, the patient showed mild anemia, no cervical lymphadenopathy or thyromegaly, and bronchiectasis features identified by lung auscultation findings. We thus reached a working diagnosis of disseminated tuberculosis including the larynx and lungs. The results of the blood profile showed normocytic normochromic anemia, low Hb, and high ESR. Fungal stain, gene X-pert for MTB/PCR, and microscopic analysis of the sputum were all normal, and the sputum C/S was consistent with the growth of normal flora. Vocal cords were normal, and fiber optic laryngoscopy revealed a swollen arytenoid region and granulo-nodularity in the posterior larynx. Under gross examination, the biopsy sample was found to consist of irregular grayish-white soft tissue fragments. Histology revealed granulation tissue, which was heavily infiltrated with acute and chronic inflammatory cells, as well as a small number of multinucleated giant cells. Furthermore, we used GMS and Pas staining to look for fungus, and the results showed round to oval yeast that was consistent with histoplasmosis. The fungus Histoplasmacapsulatum, which is a dimorphic fungus causes histoplasmosis, one of the most common causes of chronic granulomatous diseases.In North America, histoplasmosis is the most prevalent type of endemic mycosis. A portion of Africa, Australia, and Eastern Asia, especially India and Malaysia, are among the other endemic areas. Pharyngeal and laryngeal infections caused by Histoplasmacapsulatum are an uncommon manifestation that usually refers to the mucocutaneous type of chronic disseminated dissemination. The first signs and symptoms typically include fatigue malaise, loss of weight, hoarseness of voice, dysphagia, and odynophagia. Being a rare occurrence, laryngeal histoplasmosis is frequently misdiagnosed, which can have disastrous consequences for the patient. Diagnosis difficulties are probably one of the explanations for the small number of documented cases. When a patient exhibits symptoms of granulomatous inflammation or laryngeal masses, the physician should be aware of the possibility of laryngeal histoplasmosis and take it into consideration when making a differential diagnosis.Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 173-174